TAMI-01. NEOADJUVANT PD-1 ANTIBODY BLOCKADE REMODELS THE IMMUNE MICROENVIRONMENT OF METASTATIC BRAIN TUMORS. (9th November 2020) - Sun, Lu; Kienzler, Jenny; Lee, Alexander; Chow, Frances; Chavez, Carolina; Yong, William; Everson, Richard; Kim, Won; Hugo, Willy; Prins, Robert
Abstract: Brain metastases (BM) commonly arise in patients with melanoma, lung, and breast cancer. Currently, there are limited options for GBM and BM patients who have failed the first-line standard treatment, underscoring the importance of developing new therapeutic strategies. Last year, we and other groups evaluated the neoadjuvant timing of anti-PD-1 checkpoint blockade therapy in recurrent GBM (rGBM) patients, which resulted in a modest survival benefit. In light of the known effectiveness of anti-PD-1 as a systemic therapy to control melanoma and non-small cell lung cancer BM, we set out to study the anti-tumor immune response of BM patients to anti-PD-1 in the neoadjuvant setting. We posited that neoadjuvant anti-PD-1 in patients with BM would result in a stronger antitumoral immune response, which could be quantified at the single cell level. To test this, we made use of contemporary single cell techniques, including multiplex immunofluorescence, time-of-flight mass cytometry (CyTOF) and single-cell RNA sequencing (scRNAseq), to characterize the intratumoral immune cell populations and their transcriptomic profiles. We found that neoadjuvant anti-PD-1 significantly increased the number of tumor infiltrating T lymphocytes in BM compared to rGBM (2.5 fold in BM, p= 0.02 vs. 1.4 fold in rGBM, p= 0.19). Multiplex immunofluorescence analysis of T cells in BM samples revealed a change from T cell exclusion to a diffusely infiltrating phenotype after anti-PD-1 treatment. Importantly, BM showed a higher fraction of effector/cytotoxic T cells compared to rGBM (7.3% vs. 0.9% of lymphoid cells, p= 0.005) and anti-PD-1 further enhanced this population. In the myeloid compartment of BM, neoadjuvant anti-PD-1 increased the frequency of HLA-DR+CD206- M1-like macrophages, implicating a pro-inflammatory microenvironment. In summary, our study delineated the immune cell subtypes altered by neoadjuvant anti-PD-1 and offers insights into new combination therapies that can help understand the clinical efficacy of immunotherapy for BM and GBM patients.